Pericytes regulate the blood–brain barrier - Armulik, Annika; Genové, Guillem; Mäe, Maarja; Nisancioglu, Maya H.; Wallgard, Elisabet; Niaudet, Colin; He, Liqun; Norlin, Jenny; Lindblom, Per; Strittmatter, Karin; Johansson, Bengt R.; Betsholtz, Christer (Nature (London), 2010)
Building the blood–brain barrier The blood–brain barrier is a gatekeeper between the central nervous system and the rest of the body, and is made up of vascular endothelial cells. Previous work upheld the notion that the barrier was formed postnatally as a result of signalling from non-neuronal cells called astrocytes to endothelial cells. Now, two independent studies demonstrate that the barrier is in fact formed during embryogenesis, with the critical factor being the interaction between blood-vessel-surrounding cells called pericytes and epithelial cells. A better understanding of the tight relationship between pericytes, neuroendothelial cells and astrocytes in blood–brain barrier function will contribute to our understanding of the breakdown of the barrier during central nervous system injury and disease. The blood–brain barrier (BBB) is made up of vascular endothelial cells and was thought to have formed postnatally from astrocytes. Two independent studies demonstrate that this barrier forms during embryogenesis, with pericyte/endothelial cell interactions being critical to regulate the BBB during development. A better understanding of the relationship among pericytes, neuroendothelial cells and astrocytes in BBB function will contribute to our understanding of BBB breakdown during central nervous system injury and disease. The blood–brain barrier (BBB) consists of specific physical barriers, enzymes and transporters, which together maintain the necessary extracellular environment of the central nervous system (CNS) 1 . The main physical barrier is found in the CNS endothelial cell, and depends on continuous complexes of tight junctions combined with reduced vesicular transport 2 . Other possible constituents of the BBB include extracellular matrix, astrocytes and pericytes 3 , but the relative contribution of these different components to the BBB remains largely unknown 1 , 3 . Here we demonstrate a direct role of pericytes at the BBB in vivo . Using a set of adult viable pericyte-deficient mouse mutants we show that pericyte deficiency increases the permeability of the BBB to water and a range of low-molecular-mass and high-molecular-mass tracers. The increased permeability occurs by endothelial transcytosis, a process that is rapidly arrested by the drug imatinib. Furthermore, we show that pericytes function at the BBB in at least two ways: by regulating BBB-specific gene expression patterns in endothelial cells, and by inducing polarization of astrocyte end-feet surrounding CNS blood vessels. Our results indicate a novel and critical role for pericytes in the integration of endothelial and astrocyte functions at the neurovascular unit, and in the regulation of the BBB.